2005
DOI: 10.1074/jbc.m411541200
|View full text |Cite
|
Sign up to set email alerts
|

The Met-196 → Arg Variation of Human Tumor Necrosis Factor Receptor 2 (TNFR2) Affects TNF-α-induced Apoptosis by Impaired NF-κB Signaling and Target Gene Expression

Abstract: Tumor necrosis factor-␣ (TNF-␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 58 publications
2
55
0
2
Order By: Relevance
“…Both INF and ETA are able to reduce STAT3 phosphorylation to a similar degree in cultured T cells taken from patients with CD. It may well be the neutralization of sTNF that may be important in decreasing STAT3 signaling as sTNF acts in an autocrine fashion to regulate STAT3 [49].…”
Section: Effect On Intracellular Signalingmentioning
confidence: 99%
“…Both INF and ETA are able to reduce STAT3 phosphorylation to a similar degree in cultured T cells taken from patients with CD. It may well be the neutralization of sTNF that may be important in decreasing STAT3 signaling as sTNF acts in an autocrine fashion to regulate STAT3 [49].…”
Section: Effect On Intracellular Signalingmentioning
confidence: 99%
“…We previously showed that a nonsynonymous coding SNP, rs1061622 (Met196Arg), significantly alters TNFR2-mediated NF-kB activation and target gene expression (20). Moreover, haplotypes in the 39untranslated region (UTR) have been reported to affect TNFR2 expression by influencing messenger ribonucleic acid (mRNA) decay rate (21).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…The functionally relevant TNFRSF1B polymorphisms rs1061622, rs1061624, rs5030792, and rs3397 (20,21,28) were genotyped in the SAC population. All markers were in Hardy-Weinberg equilibrium in the control group.…”
Section: Analysis Of Tnfrsf1b Snps In Sacmentioning
confidence: 99%
“…The (CA) n repeat has been found to be associated with essential hypertension, hypercholesterolemia, coronary artery disease, familial combined hyperlipidemia and diabetic neuropathy (Glenn et al 2000;Benjafield et al 2001a, b;Geurts et al 2000). M196R is postulated to affect the proteolytic cleavage of the membrane bound TNFR2 to soluble form, TNF binding and/or TNF induced apoptosis by impaired NF-jB signaling (Stark et al 2003;Till et al 2005). Also, a haplotype including rs3397 in 3 0 UTR which alters TNFR2 stability and activity is associated with insulin resistance in young diabetic subjects (Puga et al 2005;Fernandez-Real et al 2000).…”
Section: Introductionmentioning
confidence: 99%